2017
DOI: 10.1007/978-1-4939-7262-3_22
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of the Plant Exocyst Complex

Abstract: The exocyst, conserved from yeast to plants to mammals, is a hetero-octameric complex that mediates tethering of secretory vesicles to designated sites on the plasma membrane during polarized exocytosis. Because structural studies of the intact exocyst complex have been greatly limited by the low yields of purified proteins, many aspects of the exocyst functions remain poorly understood. Here, we present the protocols for the isolation and purification of the recombinant and the native plant exocyst complex. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…41 MVBs can fuse with autophagosomes or directly with lysosomes after autophagy activation. 42 Fader et al proposed that autophagy increases the fusion of MVBs with autophagosomes, which directly increases the degradation of MVBs and eventually reduces exosome release. 43 Recent studies have suggested that cellular ho-meostasis decides the degradation or secretion of exosomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 MVBs can fuse with autophagosomes or directly with lysosomes after autophagy activation. 42 Fader et al proposed that autophagy increases the fusion of MVBs with autophagosomes, which directly increases the degradation of MVBs and eventually reduces exosome release. 43 Recent studies have suggested that cellular ho-meostasis decides the degradation or secretion of exosomes.…”
Section: Discussionmentioning
confidence: 99%
“…These results provided additional evidence supporting the formation of the exocyst in cells, with Sec3 and Exo70 located at the plasma membrane to promote the attachment of the exocyst to the membrane and with Sec10 acting as part of the central hub of the exocyst. 41,42 Sec10 knockdown inhibited the delivery of vesicles to the membrane, causing Sec3 and Exo70 on the membrane to have fewer vesicles to bind to. In contrast, Sec3 or Exo70 knockdown did not affect the formation of the exocyst, except with vesicles tethered to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%